Design and manufacture of Fiberglass Pipe Cutting Machine with Adjustable Holder - Rizal Indrawan (International Journal of Science, Engineering, and Information Technology, 2022)
Fiberglass is a material that is used for several products. This material was chosen because it has many advantages compared to other materials, namely it has better resistance, relatively affordable production costs and is easy to shape. PT.X is one of the manufacturing companies engaged in fiberglass, namely the manufacture of pipes and body from vehicles. In this case study the company still uses hand milling and manual processing. Fiberglass pipe in this company is molded indirectly to the size requested by the customer, therefore a cutting process is needed to get the required pipe length. The blade used specifically is a diamond-coated cutting blade because the fiber material is not heat-resistant. In this research, the researcher wants to design a fiberglass pipe cutting machine with an adjustable holder that can be adjusted so that it can cut various pipe sizes. Making the design of this machine is done using Fusion 360 software. The making of the machine includes the cutting process, grinding process, and welding process. The machine can cut a pipe with a diameter of 100 mm in 20 seconds and for a pipe with a diameter of 500 mm in 1 minute 20 seconds.